Comparison of Posterior Retroperitoneoscopic Adrenalectomy Versus Lateral Transperitoneal Laparoscopic Adrenalectomy for Adrenal Tumors: A Systematic Review and Meta-Analysis - Meng, Chunyang; Du, Chunxiao; Peng, Lei; Li, Jinze; Li, Jinming; Li, Yunxiang; Wu, Ji (Frontiers in Oncology, 2021)
Objective: To discuss the differences in the effectiveness and security for adrenal tumors by posterior retroperitoneoscopic adrenalectomy (PRA) and lateral transperitoneal adrenalectomy (LTA). Methods: We systematically searched PubMed, Embase and Cochrane Library, and the date was from above database establishment to November 2020. Stata 16 was used for calculation and statistical analyses. Results: Nine studies involving eight hundred patients were included. The following differences were observed in favor of PRA vs LTA: less operative time (MD: -22.5; 95%CI -32.57 to -12.45; P=0.000), Fewer estimated blood loss (MD: -15.17; 95%CI -26.63 to -3.72; P=0.009), lower intensity of postoperative pain (MD: -0.56; 95%CI -1.05 to -0.07; P=0.026), shorter length of hospital stay (MD: -1.15; 95%CI -1.94 to -0.36; P=0.04). No differences were shown in conversion rate (OR 2.07; 95%CI 0.71 to 6.03; P=0.181) and complications (OR 0.85;95% CI 0.46 to 1.56; P=0.597). Conclusions: Posterior retroperitoneoscopic adrenalectomy was clinically superior to lateral transperitoneal adrenalectomy for adrenal tumors in operative time, estimated blood loss, length of hospital stay, and postoperative pain. Only in term of conversion rate and complications, both were similar. Keywords: adrenal tumor, adrenalectomy, posterior retroperitoneoscopic adrenalectomy, lateral transperitoneal adrenalectomy, meta-analysis.